Relationship between serum IgG4 concentrations and atherosclerotic coronary plaques assessed by computed tomographic angiography. Issue 3 (March 2016) - Sakamoto, Aiko; Ishizaka, Nobukazu; Imai, Yasushi; Uehara, Masae; Ando, Jiro; Nagai, Ryozo; Komuro, Issei
Abstract: Background: Immunoglobulin G4 (IgG4)-related immuno-inflammation has been suggested to affect the development of coronary artery atherosclerosis. The aim of this study was to analyze the association of serum IgG4 concentrations with calcified and non-calcified coronary plaques. Methods: Serum IgG4 concentrations were measured in 263 patients who underwent 320-slice coronary computed tomographic (CT) angiography. Vulnerable coronary plaques were evaluated for CT plaque characteristics, including low-density plaque (LDP), positive remodeling, and spotty calcification. Results: Serum concentrations of IgG4 were significantly higher in patients with non-calcified plaque (NCP) than in those without (32.2 mg/dL vs. 23.7 mg/dL, p  = 0.029). By contrast, the median serum IgG4 concentrations in patients with and without calcified plaque were 31.2 mg/dL and 26.2 mg/dL, respectively ( p  = 0.107). Serum IgG4 concentrations were significantly elevated in patients with LDP (33.5 mg/dL vs. 26.9 mg/dL, p  = 0.002) and in those with positive remodeling (31.4 mg/dL vs. 28.4 mg/dL, p  = 0.039) than in those without. Patients with spotty calcification also had significantly higher serum IgG4 concentrations than those without (32.1 mg/dL vs. 24.9 mg/dL, p  = 0.049). In age- and gender-adjusted logistic regression analysis, the highest IgG4 quartile (≥56.7 mg/dL) was significantly associated with LDP with an odds ratio of 2.49 (95% CI, 1.15–5.36, p  = 0.020). Conclusions: Serum IgG4 concentrations were significantly associated with NCP, especially with LDP, suggesting that IgG4-related immuno-inflammation may play a role in coronary plaque vulnerability.